Analisis Kapasitas Kelembagaan Badan Perencanaan Pembangunan Daerah Banda Aceh dalam mendorong Pelaksanaan Inovasi Daerah di Kota Banda Aceh - Rahmanda, Alfi Rizky (Jurnal Transformasi Administrasi, 2023)
Problems in the public sector or government need to be solved through innovation. Innovation should be the focus of the government to do this with the aim of producing quality public services, shortening service time, and cutting bureaucracy. Law Number 23 of 2014 concerning Regional Government, has indicated that the obligation and authority for innovation does not only belong to the Central Government, but that the Regional Government has the same obligation. In increasing the innovation of a region, a strong and optimal research and development institution is needed in the framework of its implementation. This paper aims to look at the institutional capacity of the Banda Aceh City Regional Development Planning Agency (BAPPEDA) in encouraging the implementation of regional innovations in Banda Aceh City. This research uses descriptive qualitative method with data collection in the form of interviews with a number of informants, as well as through library research. The result of this research is that there is a need for institutional capacity building for BAPPEDA Kota Banda Aceh to encourage the implementation of regional innovations. It is necessary to increase the joint commitment of all parties, the existence of good conducive leadership, as well as institutional structural reform of BAPPEDA Banda Aceh. In addition, there is a need for an in-depth study related to the establishment of the Regional Innovation Research Agency (BRIDA) in order to encourage the implementation of regional research and innovation in the City of Banda Aceh.